Nghiên cứu các nguồn nước tại Bắc Bình trên cơ sở phân tích các yếu tố khí tượng - Văn, Phan Thị Kim (Vietnam Journal of Earth Sciences, 2018)
The study of water resource for management of aquifer recharge at Bac Binh area based on analyzing meteorological factors